"They Can't Find Anything Wrong with Him, Yet": Mothers' experiences of parenting an infant with a prenatally diagnosed copy number variant (CNV). Issue 2 (7th November 2016) - Werner‐Lin, Allison; Walser, Sarah; Barg, Frances K.; Bernhardt, Barbara A.
Abstract : Chromosome microarray (CMA) testing is used widely in prenatal settings. Some copy number variants (CNVs) detected using CMA are associated with variable or uncertain phenotype and/or possible neurocognitive involvement. Little is known about parenting an infant following such findings. Researchers conducted interviews with 23 mothers of infants diagnosed prenatally with a potentially pathogenic CNV to elicit perspectives on the child's development and disclosure of results to others. Interviews were audiotaped and analyzed for common themes. Most respondents reported their infants were developing typically. The majority expressed concern about their child's future development given the CNV. They reassured themselves their child was unaffected by: comparing him/her to siblings, scrutinizing the child's appearance and behavior, or following provider reassurances. Even without developmental and neurological concerns, some remained acutely observant of their child's neurocognitive development, leading to enrollment in early intervention or ongoing medical assessments. Mothers who were unconcerned stated they would likely attribute atypical behavior or developmental to the CNV. All interviewees shared the result with pediatricians, relatives, or friends, and many shared across groups. Most shared information with pregnant friends considering prenatal testing, but withheld partial or full information from family members due to stigma, lack of understanding, inability to explain the CNV, or presumptions that the child was unaffected. Research must address the long‐term consequences of returning uncertain results for parent‐child bonding and costs of ongoing assessment and early intervention for typically developing children. Follow up appointments will permit providers to screen for anxiety and assuage worry in the absence of symptoms. © 2016 Wiley Periodicals, Inc.